FUNGSI-FUNGSI TATANIAGA KOMODITAS UBI KAYU DI KOTA MANOKWARI - Cicilia M.A. Pandiangan; Yustina L.D. Wambrauw; Uria, Darmawanto (Sosio Agri Papua, 2021)
Marketing Finction is defined as service or activities and actions in distribution processes of goods from producers to consumers. The objective of this research is to know the functions that done by cassava sellers in Manokwari. The method of this reserach is description with describing situation and condition of cassava seller in some markets there are Wosi, Sanggeng and Borobudur. The result shows that all of respondents are farmers that sell their own products and majority of farmers doing six functions ( selling, transportating,grading and standaritation, packaging, risk managing and costing). On the other hand, there are three functions that not conducted by sellers are Buying, Saving, and proccesing and market information system.